The long-term impact of combat exposure on health, interpersonal, and economic domains of functioning. (1st November 2016) - Sheffler, Julia L.; Rushing, Nicole C.; Stanley, Ian H.; Sachs-Ericsson, Natalie J.
Abstract : Purpose: Wartime combat exposure is linked to a broad array of negative outcomes. The current study identified potential differences between middle-to-older aged men exposed to combat and those not exposed for physical health, interpersonal, and economic functioning over 10 years. Post-traumatic stress disorder (PTSD) and social support were examined as moderators between combat exposure and outcomes. Methods: Data from the National Comorbidity Survey, baseline and 10-year follow-up, were utilized. Only men aged 50–65 at follow-up ( N = 727) were included. Group differences between combat and non-combat men were examined. Regression analyses were performed to examine relationships between earlier combat and health, interpersonal, and economic outcomes over time, while controlling for important covariates. Results: Combat-exposed men were at increased risk for asthma, arthritis/rheumatism, lung diseases, headaches, and pain; they also had greater marital instability. However, combat-exposed men reported economic advantages, including higher personal earnings at follow-up. For combat-exposed men, PTSD did not increase risk for headaches; however, PTSD in non-combat men was associated with increased risk for headaches at follow-up. Whereas combat-exposed men with higher levels of social support were less likely to report chronic pain at follow-up, there were no group differences in pain at lower levels of social support. Implications: Individuals who experience combat may be susceptible to later health and marital problems; however, as combat-exposed men age, they demonstrate some resilience, including in economic domains of life. Given that consequences of combat may manifest years after initial exposure, knowledge of combat exposure is necessary to inform treatments and the delivery of disability benefits.